Communication Analysis of the Rembang Regency General Elections Commission Regarding the 2024 General Election Re-voting - Ludina, Deva Anggreani; Rohid, Nibrosu (Jurnal Komunikasi Profesional, 2025)
This study aims to analyse the public communication strategies implemented by the Rembang Regency General Elections Commission (KPU) during the implementation of the 2024 General Election Re-voting (PSU). As a corrective mechanism, PSU requires effective communication to maintain public trust and institutional legitimacy. This research employs a descriptive-interpretative qualitative approach, with the leadership of KPU Rembang, including the Chairperson and members as research subjects. Data were collected through in-depth interviews, participant observation, and official document studies, followed by a thematic analysis. The results indicate that KPU Rembang implemented a multi-channel, adaptive, educational, and transparent communication approach. The communication strategy was tailored to audience characteristics, utilising face-to-face interactions, print media, and digital platforms. Human resource preparation through training and polling station (TPS) simulations ensured that messages were delivered consistently and accurately. This approach reflects the principles of media richness, audience-centred communication, crisis communication, and institutional legitimacy, enabling the public to clearly understand the objectives and procedures of the re-voting process. The study also found that strong internal coordination and consistent socialisation materials enhanced communication effectiveness, despite challenges in reaching populations with low political literacy. These findings confirm that KPU’s public communication plays a crucial role in building community understanding, safeguarding public trust, and maintaining the integrity of the re-voting process.